Study of Radiation Dose in Common Fluoroscopy Methods in Adult Patients Referred to Namazi Hospital in Shiraz during 2018-2019 - Dosideh, Sara; Ravanfar Haghighi, Rezvan; jaam, Ahmadreza; Zarei , Fariba (Shahroud Journal of Medical Sciences, 2025)
Background: The basis of the largest source of human radiation exposure is ionizing radiation used in medical and clinical sciences. This study aimed to investigate the radiation dose in common fluoroscopy methods in adult patients referred to Namazi Hospital in Shiraz in 2018.Methods: This cross-sectional study was conducted on 600 adult patients (18 years and older) who were referred to Namazi Hospital in Shiraz for fluoroscopy. Data were collected using a checklist prepared from patient records, including demographic information of patients including age, gender, height, weight, and BMI, and information related to fluoroscopy including type of fluoroscopy, duration of fluoroscopy, and dose of fluoroscopy. Fluoroscopy-related data were extracted from the PACS system or manually based on the final report of each patient's file. Data were analyzed using SPSS18 software and independent t-tests, ANOVA, and Pearson correlation coefficient.Results: The mean age of the patients was 48.56 ± 15.59 years (18-90 years). 36.5% were male and 63.5% were female. The mean BMI was 24.85 ± 4.87 (13.43-67.20). The most commonly used fluoroscopy method was B. SW (43.7%), followed by DEFECO (23.5%), and the least used method was RCG in only 10 patients (1.7%). The mean time of fluoroscopy was 2.08 ± 1.51 (0.1-9.60 minutes). The mean dose received in all fluoroscopy methods was 1650.42. A statistically significant relationship was observed between the dose of fluoroscopy and the duration of fluoroscopy (r=0.0403. P-value<0.001) and BMI (r=0.249, P-value<0.001), and the age of the patients had no significant relationship with the dose received in fluoroscopy (r=0.075, P-value=0.066). The difference in the mean duration of fluoroscopy based on different fluoroscopy methods was statistically significant (P-value<0.001). The difference in the mean dose of fluoroscopy based on different fluoroscopy methods was statistically significant (P-value<0.001).Conclusions: In general, the results of the study showed that most fluoroscopy was performed with the barium swallow method. With increasing fluoroscopy duration and BMI, the dose received by the patient increased significantly, and the highest dose received was observed in the barium enema method and the longest fluoroscopy time was observed in the UGI method, but further and better investigation is still needed to identify the influencing factors.